(untitled) (Bangladesh Journal of Pharmacology, 2016)
Sphagnum palustre (a moss) has been traditionally used in Korea for the cure of several diseases such as cardiac pain and stroke. In this research, the inhibitory effect of S. palustre on aromatase (cytochrome P450 19, CYP19) activity was studied. [1?-3H] androstenedione was used as a substrate and incubated with S. palustre extract and recombinant human CYP19 in the presence of NADPH. S. palustre extract inhibited aromatase in a concentration-dependent manner (IC50 value: 36.4 ± 8.1 µg/mL). To elucidate the major compounds responsible for the aromatase inhibitory effects of S. palustre extract, nine compounds were isolated from the extract and tested for their inhibition of aromatase activity. Compounds 1, 6, and 7 displayed aromatase inhibition, while the inhibition by the other compounds was negligible. Video Clip of Methodology: Aromatase enzyme activity: 4 min 16 sec Click to watch